Development of Visual Novel Games as Learning Media for the History of Indonesia's Independence - Muhammad Hanif Khoiruddin; Zain Hazmi Zain Bahari; Mariwan Salih Kaka; Suchart Saenpich (Journal of Educational Technology and Learning Creativity, 2023)
Purpose of the study: This study aims to develop an Android-based visual novel game using material from the history of Indonesian independence and to determine the level of feasibility by going through a feasibility test on the Visual Novel Game application of the History of Indonesian Independence. Methodology: This research is research and development type. Research and development is research with the aim of conducting research and innovating in making a product. System development in this study uses the Evolutionary Prototype method. With this method, the prototype can be continuously developed until the prototype fulfills the functions and procedures required by the system. Main Findings: The results showed that the use of renpy as an engine facilitated the process of making the Visual Novel Independence Game application. Then, the independence game application is good and can be said to be appropriate as a learning medium. From the feasibility test summary, the feasibility percentage of the Visual Novel Merdeka game has an average of 76.6%. This percentage is categorized as having good eligibility. In terms of the material for the independence game application, it is also in accordance with the needs of teaching materials for grade 11 high school or vocational school. Novelty/Originality of this study: This application is light, easy to understand and has a small size so that it will make it easier to use.